Endoscopic Resection of Tuberculum Sellae Meningiomas - Gadgil, Nisha; Thomas, Jonathan G.; Takashima, Masayoshi; Yoshor, Daniel (Journal of Neurological Surgery Part B: Skull Base, 2013)
Objective To evaluate the results of endoscopic transnasal resection of tuberculum sellae meningiomas (TSMs) as compared with transcranial approaches.Design We retrospectively analyzed five patients who underwent endoscopic endonasal resection of TSM and performed a comprehensive review of articles published between 2000 and 2012 describing the operative treatment of TSMs.Results Gross total resection (GTR) was achieved in four patients (80%). Transient diabetes insipidus occurred in three patients (60%). Preoperative visual field deficit resolved in all patients. Cerebrospinal fluid (CSF) leak occurred in one patient. Analysis of published studies included 1,026 transcranial and 144 transnasal cases. GTR was achieved in 85% of transcranial and 72% of transnasal cases. Visual field deficit improved in 65% of transcranial and 82% of transnasal cases. Rate of diabetes insipidus and CSF leak was higher in the transnasal series. Rate of GTR and visual improvement was higher in endoscopic endonasal as compared with microsurgical transnasal series.Conclusion The literature supports transsphenoidal surgery for the resection of TSMs with significant optic nerve compromise and limited lateral extension. This approach may have an equivalent if not superior outcome over transcranial surgery in visual outcome. CSF leaks are still a challenge but may improve with the use of vascularized nasoseptal flaps.
Keywords: tuberculum sellae; meningioma; endoscopic approach; transcranial